Effects of intermittent visual feedback on EEG characteristics during motor preparation and execution in a goal-directed task - Yu, Baobao; You, Yimeng; Li, Yahui; Chen, Jiaqi; Zhou, Huilin; Wang, Jun; Huang, Junchen; Fan, Weinv; Xu, Jialin; Zuo, Guokun (Frontiers in Human Neuroscience, 2024)
IntroductionVisual feedback plays a crucial role in goal-directed tasks, facilitating movement preparation and execution by allowing individuals to adjust and optimize their movements. Enhanced movement preparation and execution help to increase neural activity in the brain. However, our understanding of the neurophysiological mechanisms underlying different types of visual feedback during task preparation and execution remains limited. Therefore, our study aims to investigate the impact of different types of visual feedback on movement-related brain activity in goal-directed tasks, in order to identify more effective forms of visual feedback in goal-directed tasks.MethodsThe electroencephalographic (EEG) data from 18 healthy subjects were collected under both continuous and intermittent visual feedback conditions during a goal-directed reaching task. We analyzed the EEG characteristics of the event-related potential (ERP), event-related synchronization/desynchronization (ERS/ERD) in all subjects during motor preparation and execution of the goal-directed reaching task.ResultsThe results showed that, the amplitude of motor-related cortical potential (MRCP) in subjects was larger in the intermittent visual feedback condition compared to the continuous visual feedback condition during motor preparation, and the amplitude was largest at the CPz electrode. Additionally, mu-ERD was more pronounced during both motor preparation and execution under intermittent visual feedback condition.DiscussionIn conclusion, intermittent visual feedback enhanced the characteristics of subject’s brain activation and cortical excitability in the time and time-frequency domains.